Wavepacket models for subsonic twin jets using 3D parabolized stability equations - Rodríguez, Daniel; Jotkar, Mamta R.; Gennaro, Elmer Mateus (Cellule MathDoc/Centre Mersenne, 2018)
An extension of the classical parabolized stability equations to flows strongly dependent on the two cross-stream spatial directions and weakly dependent on the streamwise one is applied to model the large-scale structures present in twin-jet configurations. The existence of these unsteady flow structures, usually referred to as wavepackets, has been demonstrated in the literature for both subsonic and supersonic round jets, along with their relation to the generation of highly directional noise emitted in the aft direction. The present study considers twin-jet configurations with different separations at high Reynolds number and subsonic conditions. The existing instability modes for the twin-jet mean flow, their dependence on the separation of the two jets, and the interaction between the wavepackets originating from the two jets is investigated here. Arising from the axisymmetric mode for single round jets, two dominant modes are found for twin jets: a varicose one, relatively insensitive to jets’ proximity, but likely to be efficient in radiating noise; a sinuous one, whose amplification is strongly dependent on the jets’ distance, and which can be expected to produce weaker acoustic signatures.
Keywords: Flow instability; Parabolized Stability Equations; Turbulence modelling; Twin jets; Wavepackets